Large-Scale Production of Nanographite by Tube-Shear Exfoliation in Water - Blomquist, Nicklas (PLoS One, 2016)
The number of applications based on graphene, few-layer graphene, and nanographite is rapidly increasing. A large-scale process for production of these materials is critically needed to achieve cost-effective commercial products. Here, we present a novel process to mechanically exfoliate industrial quantities of nanographite from graphite in an aqueous environment with low energy consumption and at controlled shear conditions. This process, based on hydrodynamic tube shearing, produced nanometer-thick and micrometer-wide flakes of nanographite with a production rate exceeding 500 gh(-1) with an energy consumption about 10 Whg(-1). In addition, to facilitate large-area coating, we show that the nanographite can be mixed with nanofibrillated cellulose in the process to form highly conductive, robust and environmentally friendly composites. This composite has a sheet resistance below 1.75 Ω/sq and an electrical resistivity of 1.39×10(-4) Ωm and may find use in several applications, from supercapacitors and batteries to printed electronics and solar cells. A batch of 100 liter was processed in less than 4 hours. The design of the process allow scaling to even larger volumes and the low energy consumption indicates a low-cost process.